2010
DOI: 10.1542/peds.2009-3079
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Assessment Method and Baseline Characteristics in a Mixed Longitudinal Study of Girls

Abstract: OBJECTIVES The objective of this study was to describe the assessment methods and maturation status for a multisite cohort of girls at baseline recruitment and at ages 7 and 8 years. METHODS The method for pubertal maturation staging was developed collaboratively across 3 sites. Girls at ages 6 to 8 years were recruited at 3 sites: East Harlem, New York; greater Cincinnati metropolitan area; and San Francisco Bay area, California. Baseline characteristics were obtained through interviews with caregivers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
5
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(251 citation statements)
references
References 45 publications
3
234
5
5
Order By: Relevance
“…During recent decades, age at pubertal onset seems to have markedly declined in girls (2,3,4,5,6) and to a lesser extent in boys (6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…During recent decades, age at pubertal onset seems to have markedly declined in girls (2,3,4,5,6) and to a lesser extent in boys (6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] An expert panel convened in 2003 by Serono Symposia International, Inc, concluded that US girls were entering puberty at an earlier age than 40 years ago. 1 One of the key studies leading to this conclusion, conducted by the American Academy of Pediatrics (AAP), found girls were typically developing about a year earlier than previously assumed.…”
mentioning
confidence: 99%
“…Esta recomendación ha sido cuestionada posteriormente por la metodología del estudio y no ser representativa de la población estadounidense en general (47) . Sin embargo, datos más recientes de los Estados Unidos (48) muestran un aumento en el número de niñas blancas y negras que presentan telarquía antes de los 8 años.…”
Section: Comportamiento De Las Características Puberales De Las Niñasunclassified